The Influence of Peer Social Environment and Type of Vape as a Medium of Self-Image among Late Adolescents: A Study in Bandar Lampung - Hero Satria Novara Cahya; Pairulsyah; Damar Wibiosono (Master's Program in Sociology, Faculty of Social and Political Sciences, Universitas Negeri Surabaya, 2026)
This study examines the influence of peer environment and types of vape devices on the self-image of late adolescents who use vape in Bandar Lampung City. A quantitative survey method was employed involving 50 respondents selected through purposive sampling. Data were analysed using multiple linear regression. The t-test findings indicate that the peer environment variable (X1) yields a significance value of 0.054 (> 0.05), suggesting no statistically significant effect on self-image (Y), whereas the type of vape device (X2) yields a significance value of 0.016 (< 0.05), indicating a statistically significant effect. Simultaneously, the F-test reveals that both variables jointly demonstrate a significant influence on self-image, with a significance value of 0.001 (< 0.05). The correlation coefficient (R) of 0.515 indicates a moderate association, whilst the coefficient of determination (R Square) of 0.265 suggests that 26.5% of the variation in self-image is explained by these variables, with the remaining 73.5% attributed to factors beyond the scope of this study. The peer environment primarily plays a role in adolescents' initial decision to engage in vaping, whereas the type of vape device exerts a more substantial influence on shaping self-image as a form of self-expression within social contexts. Situating these findings within a Global South perspective further reveals that weak regulatory frameworks, social media marketing, and peer network dynamics collectively amplify the symbolic role of vape type in adolescent identity construction, reflecting structural patterns shared across rapidly urbanising societies beyond the Indonesian context.